Vulkanostratigrafi dan Implikasi Terhadap Tanah Longsor Daerah Serang dan Sekitarnya, Kecamatan Salawu, Kabupaten Tasikmalaya, Provinsi Jawa Barat - Rizqi, Al Hussein Flowers; Aprilia, Adinda; Tedja Trisnaning, Paramitha (ReTII, 2024)
The research area is administratively located in the Serang area and its surroundings, Salawu District, Tasikmalaya Regency, West Java Province. Geographically, the research area is at coordinates 7Â°20’24" - 7Â°24’53" South Latitude and 108Â°1’19" - 108Â°4’37" East Longitude. Physiographically, it is included in the Bandung Zone. This research aims to provide an overview of geological conditions such as geomorphological aspects, lithological distribution, stratigraphy, geological structure, geological history and environmental geology in the research area. The research method used is literature study and surface geological mapping using the concept of volcanostratigraphy to obtain primary data using a landsat image analysis and petrographic analysis approach. Based on this research, it is known that the geomorphological units that make up the research area include the Cikuray structural denudational unit (D1), the Cikuray lava flow ridge geomorphological unit, the Karacak lava flow ridge geomorphological unit and the Galunggung lava flow unit. Stratigraphically, the research area is composed of six rock units from old to young, namely the Karcak lava breccia unit, the Karacak tuff unit, the Cikuray pyroclastic breccia unit, the Cikuray tuff unit, the Galunggung lava breccia unit and the Cikuray lava deposit unit. Natural disasters in the research area are landslides of the surge type in Sukarasa Village and rotational landslides in Serang Village.